Regulating Informal Employment in Uzbekistan in Conditions of Economy Modernization - B. E. Tagaev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the notion of informal employment, its essence, types, structure and methodological approaches to its registration and evaluation. Different ways of defining informal employment were investigated by using various criteria, such as the type and status of the enterprise, employment, institutional standards and informal economy. Social and economic consequences of informal employment development were found, as well as its role on labour market, which fosters (in line with negative factors) a drop in actual unemployment, a decrease in tension and a rise in competition. The experience of different countries connected with cutting informal employment was studied and a conclusion was drawn about the necessity to design and adopt a complex approach that combines legal, administrative and economic steps aimed at elimination of this phenomenon. The author substantiates the necessity of complex policy covering different fields of regulation together with mechanisms of stimulation and punishment, broader goals for institution upgrading, economic reforms and changing social norms, lowering tolerance to informal labour relations. The article analyzes structural reforms taking place on labour market in Uzbekistan that are aimed at liberalization and meet international standards, including organizational and legal, which could create a favourable environment for cutting the informal employment rate. Within the frames of the research recommendations were worked out for cutting the informal employment rate with regard to global experience.